Party Education and Cadre Schools in Communist Romania. Some Preliminary Considerations - VELIMIROVICI, Felician (Studia Universitatis Babeș-Bolyai Historia, 2022)
The present lines raise the question of the necessity of a thorough study of a largely ignored chapter in the history of Romanian communism, namely the system of party education and cadre schools. If in a first phase, in Romanian post-socialist historiography, the orientation towards the research of the extremes of the system, of terror and repression has prevailed, nowadays it is at least as necessary to understand the mechanisms by which the communist system was perpetuated and regenerated. Party schools were more than mere instruments of indoctrination, manipulation and propaganda, they represented key institutions that fully contributed to the construction of the system itself. Article history: Received: 22.06.2022; Revised: 04.08.2022; Accepted: 04.08.2022; Available online: 15.09.2022 Rezumat: Materialul de față ridică problema necesității studierii unui capitol mai puțin cunoscut din istoria comunismului românesc, anume sistemul învățământului de partid şi al şcolilor sale de cadre. Dacă într-o primă fază, în istoriografia românească post-socialistă a predominat orientarea către cercetarea extremelor sistemului, a terorii şi represiunii, în prezent este cel puțin la fel de necesară înțelegerea mecanismelor prin care sistemul comunist s-a perpetuat şi regenerat. Şcolile de partid au fost mai mult decât simple instrumente de îndoctrinare, manipulare şi propagandă, ele reprezentând nişte instituții-cheie care au contribuit din plin la însăşi construcția sistemului. Cuvinte-cheie: învățământ politic, şcoli de partid, cadre, Partidul Comunist Român.